DISTRIBUSI SUBMIKROFOSIL (POLEN DAN FORAMINIFERA) PADA DELTA FRONT DI DELTA MAHAKAM, KALIMANTAN TIMUR - Jurnaliah, Lia; -, Winantris (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
The Research area located in the Mahakam Delta, East Kalimantan. The object of research are submicrofossils (pollen and foraminifera) in recent sample sediment derived from the delta front of Mahakam Delta. The amount of sediment that is researched as much as 29 samples. The results of the quantitative analysis showed pollen assemblage consists of 24 species of palmae, 21 species of mangrove and 117 species of non-mangrove. The collection of foraminifera consists of 82 species of small benthonic foraminifera. Based on cluster analysis, pollen assemblage consists of seven biofacies i.e. palmae-non mangrove, non-mangrove A, palmae-mangrove-non mangrove A, palmae-mangrove-non mangrove B, mangrove-non mangrove, palmae, and non-mangrove B . Similarly, foraminifera consists of seven biofacies i.e. biofacies I (Inner Shelf), biofacies II (Coastal lagoon-InnerShelf), biofacies III (Coastal bay – Inner Shelf), biofacies IV (Coastal lagoon/Coastal bay-Inner Shelf), biofacies V (Open estuary/Coastal lagoon-Inner Shelf), biofacies VI (Coastal bay/Coastal lagoon-Inner Shelf) and biofacies VII (mangrove swamp (marsh). The distribution of pollen and foraminifera in delta front suggest that the southern region was more influenced by sea compared with the northern region, and the central region is affected by tidal currents.